DISCIPLESHIP AND DIRECTIONS IN THE TAMIL SAIVAITE SPIRITUAL LIGHT OF TRADITION - Irudayaraj, Xavier (Journal of Dharma, 1980)
Any significant reflection on the theology of Guru has its corresponding ecclesiological implications. Particularly, the idea of discipleship which is inseparably linked with the idea of the Guru, presents us with an image of the Church which could deepen our understanding of certain aspects of the Mystery of the Church. As Pope Paul VI said in his opening allocation at the second session of Vat. II (Sept. 29, 1963): "The Church is a mystery. It is a reality imbued with the hidden presence of God. It lies, therefore, within the very nature of the Church to be always open to new and greater explorations."